Influence of absorption capacity on response capacity in small mexican manufacturing companies. - Demuner-Flores, María del Rosario (2021)
The absorption capacity allows companies to combine the knowledge extracted from the outside with the previously developed inside to respond to the constant changes in their environment. The purpose was to determine the influence of the acquisition, assimilation, transformation and exploitation of knowledge and its impact on the organizational response capacity of small companies. A sample of 132 small Mexican companies was used. The questionnaire’s quality was confirmed. A hierarchical regression model was determined. The results showed a significant positive relationship between acquisition, assimilation, transformation, and exploitation with the response capacity of the organization. Nevertheless, the multiple regression model excluded the exploitation of knowledge. This means that small companies benefit from external knowledge to strengthen their internal baggage, but they do not obtain the benefits of exploitation by not materializing knowledge abroad through innovation. This research reveals the SMEs need to stimulate and take advantage of their absorption capacity in the development of new products or services that respond to an increasingly demanding market